Laboratory Studies of Frost Action in Soils with Special Reference to the Clay Mineral Fraction - Poloniato, Gino A. (My University, 1973)
The laboratory cold-room and its equipment have been designed to enable studies to be made under controlled conditions of a11 frost phenomena occurring in soils which are reasonably adaptable to investigation by laboratory methods.1 Although this particular overall laboratory program incorporated various testing methods, experiments, and analyses, it was designed chiefly to determine the quantitative effects of individual variables which influence ice segregation in soils. The variables that will be discussed in this paper are as follows: (1) gradation and percent finer than 0.02mm; (2) effect of compaction; (J) percent stone; (4) penetration of 32°F temperature; (5) temperatures between frozen and unfrozen soil; (6) saturated clay in a closed system.2
Title: Laboratory Studies of Frost Action in Soils with Special Reference to the Clay Mineral Fraction, Author: Gina A. Poloniato, Location: Thode